PENGARUH MEDIA PEMBELAJARAN VIDEO TERHADAP HASIL BELAJAR GULING DEPAN SMP N 03 MUKOMUKO - Zhafran Yafi Aprilianto; Gusti Handayani, Sri; Zulbahri; Novita Sari, Dessi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the issue of low learning outcomes regarding the forward roll skill among Grade VIII A students at SMPN 03 Mukomuko. Out of 32 students, only 14 (43.75%) successfully met the Minimum Mastery Criterion (KKM) of 75, while the remaining 18 students (56.25%) scored below this threshold. The study aimed to examine the impact of using video as an instructional medium on improving the students' forward roll performance. A quantitative experimental approach was employed, specifically utilizing a one-group pretest-posttest design. The study involved the entire class of 32 Grade VIII A students, selected via total sampling. Data collection relied on a performance test assessing forward roll skills, administered both before (pretest) and after (posttest) the intervention—which consisted of showing an instructional video. Data analysis utilized a paired-sample t-test to determine the difference in mean learning outcomes between the two stages. The findings indicate a significant influence of the instructional video on the students' forward roll ability; the mean score rose from 16.44 in the pretest to 22.03 in the posttest, with a significance level of p < 0.05. Thus, it can be concluded that the use of video media helped Grade VIII A students at SMPN 03 Mukomuko improve their forward roll technique. Consequently, this medium serves as a viable creative alternative for teaching physical education in schools.